2007
DOI: 10.1177/1362361307076925
|View full text |Cite
|
Sign up to set email alerts
|

Face processing in children with autism

Abstract: Recent eye tracking studies of face processing have produced differing accounts of how and whether children with autism differ from their typically developing peers. The two groups' gaze patterns appear to differ for dynamic videos of social scenes, but not for static photos of isolated individuals. The present study replicated and extended previous research by comparing the gaze patterns of individuals with and without autism for four types of stimuli: social dynamic, social static, isolated dynamic, and isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
136
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(161 citation statements)
references
References 21 publications
11
136
1
3
Order By: Relevance
“…For example, individuals with autism are known to look at the mouth instead of the eyes, especially during dynamic social situations (Klin et al, 2002;Speer, Cook, McMahon, & Clark, 2007). Although the pattern of social deficits in autism may be more extreme than in shyness, the pattern of face scanning observed in individuals with autism may not be the same for non-clinical samples with lesser forms of social deficits such as those who are shy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, individuals with autism are known to look at the mouth instead of the eyes, especially during dynamic social situations (Klin et al, 2002;Speer, Cook, McMahon, & Clark, 2007). Although the pattern of social deficits in autism may be more extreme than in shyness, the pattern of face scanning observed in individuals with autism may not be the same for non-clinical samples with lesser forms of social deficits such as those who are shy.…”
Section: Discussionmentioning
confidence: 99%
“…This methodology allows to objectively analyze gaze pattern during the viewing of naturalistic situations or during the performance of cognitive tasks. Studies with adults and children with ASD during visualization of naturalistic social scene have shown that they have a preference for non-social information (physical details of the environment) rather than for the social information (face and eyes of characters) [20,[28][29][30]. In 2002, Klin and colleagues published the first paper using eye-tracking methodology in autism.…”
Section: Gaze Abnormalities In Autism: Eye Tracking Studiesmentioning
confidence: 99%
“…Klin, Jones, Schultz, Volkmar & Cohen (2002) carried out an eye-tracking study of naturalistic social situations and found that participants with autism spent twice as much time looking at the mouth region of faces than on the eyes, whereas non-autistic individuals look at the eye region for three times as long as the mouth region Teaching emotion 4 on average. Similarly Speer, Cook, McMahon & Clark (2007) also used eye-tracking technology and found that the participants with autism spent significantly less time looking at the eye region of dynamic social stimuli (i.e. video footage) than non-autistic participants.…”
Section: Teaching Emotion Recognition Skills To Children With Autismmentioning
confidence: 99%